2021
DOI: 10.1002/14651858.cd012823.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of psychosocial interventions for reducing parental substance misuse

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: Primary objective To assess the effectiveness of psychosocial interventions at reducing the substance misuse (alcohol and/or illicit drugs excluding tobacco) of parents with children of dependent age (from birth to 21years). Intervention impact will be examined separately for different substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 156 publications
0
20
0
Order By: Relevance
“…The appropriateness of involving the child in the intervention may be affected by the level of exposure the child has to the parent’s alcohol misuse, the risks associated with their pattern of alcohol use and the age of the child. Further, a recent meta-analysis found that parents did not reduce the frequency of their alcohol use when children were involved in psychosocial intervention sessions and it was suggested that the presence of the child may affect the parent’s engagement with the intervention ( McGovern et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriateness of involving the child in the intervention may be affected by the level of exposure the child has to the parent’s alcohol misuse, the risks associated with their pattern of alcohol use and the age of the child. Further, a recent meta-analysis found that parents did not reduce the frequency of their alcohol use when children were involved in psychosocial intervention sessions and it was suggested that the presence of the child may affect the parent’s engagement with the intervention ( McGovern et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A major review of UK child protection services highlighted the importance of preventive rather than reactive services as being more effective in improving child welfare ( Munro, 2011 ). Despite this, there is no established preventative intervention for parental alcohol misuse ( McGovern et al., 2021 ). Further, there remains uncertainty about who is best placed to respond to these lower level alcohol needs and what severity and nature of alcohol-related concern merited intervention from social care ( Hafford-Letchfield et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complexity and multilayered risk in families affected by parental substance misuse, there is growing consensus that integrated and family-focused intervention models that address the cumulative and complex nature of vulnerabilities are needed (McGovern et al, 2021;Niccols et al, 2012aNiccols et al, , 2012b. A range of intervention models have been developed and are often focused on reducing parent psychopathology and improving the capacity to parent in a sensitive and developmentally appropriate manner (Eggins et al, in press;Syed et al, 2018).…”
mentioning
confidence: 99%
“…This study targeted DVA and MH, used a brief, one-off empowerment-based approach, and treated these issues as bi-directional, offering concurrent support for DVA and MH, recognising and addressing the relationships between them. Studies targeting MH and SU often demonstrated more mixed or negative impacts on outcomes which could be related to the type of intervention delivered [128], or perhaps because they remove a trauma coping mechanism without providing additional support to manage this. There were also studies that demonstrated singular impacts on outcomes despite attempting to tackle DVA, MH, and SU in combination.…”
Section: Discussionmentioning
confidence: 99%